ANALISIS SURVEY KEPUASAN PENGGUNA TERHADAP WEBSITE BINA DARMA CAREER AND TRAINING CENTER (BDCTC) - Panjaitan, Febriyanti (Universitas Bina Darma, 2013)
In the world of education website is a place to disseminate information both from private and public institutions. Bina Darma Career and Training Center (BDCTC) is a training institute and job placement center that has a website that is www.bdctc.or.id, but the problem is that the website has not been put to good use by users that stakeholders / companies, alumni and students. To find out the problem, then the website BDCTC need to analyze the level of satisfaction of users with measurement techniques quality website that is WebQual through 3-dimensional (Usability, Information, and Service). The method of analysis used descriptive survey approach.Based on the research note that the level of satisfaction of the users of the website BDCTC 3-dimensional views of the Usability and Service does not have a significant effect on user satisfaction, while at the Information have any impact on satisfaction.The third dimension of the most dominant influence is the information. Keywords: Analysis, WebQual, stakeholders, students, alumni and quantitative descriptive methods.